Small Business: Essence, Formation and Development - Krekova, Marina M.; Shevchenko, Ekaterina V.; Shchinova, Raisa A.; Zelinskaya, Maria V.; Akhmadeev, Amir M. (International Review of Management and Marketing, 2016)
In modern life of our country, the development of small business is one of the conditions for full-fledged market economy, sustainable economic development and stability in the social sphere. Trends of modern economics say that the efficiency of the economy of the country in which a significant role in the socio-economic development assigned to small businesses. The market economy cannot properly function without a large number of small businesses are the engine of competition. The innovative approach of economic development can only be realized through the development of small and medium-sized businesses, as effective may be just a small business, which is due to rational forms of organization, new technologies and the versatility of its employees achieve success in business. Big business in our country reaches success at the expense of administrative resources, the use of capital and the functioning of the monopoly on the verge of tweaks that will not lead to effective development of economy and society. Of course, this does not refer to all major companies of the Russian economy. Keywords: small business, labor market, enterprise, market economy, management JEL Classifications: E29, J59, M11